Aragonite saturation state variation and control in the river-dominated marginal BoHai and Yellow seas of China during summer. (October 2018) - Xu, Xuemei; Zheng, Nan; Zang, Kunpeng; Huo, Cheng; Zhao, Huade; Mu, Jingli; Wang, Juying; Sun, Bing
Abstract: Based on a survey conducted from June to July 2013, aragonite saturation state variation and control in the river-dominated marginal BoHai and Yellow seas were investigated. Surface water Ωarag ranged from 2.0–3.8, whereas subsurface water Ωarag was generally lower than 2.0. Temperature changes had a strong influence on Ωarag through induced CO2 solubility changes in seawater. Riverine freshwater input decreased Ωarag in the Changjiang and Yalu river estuaries, but induced higher Ωarag in the Yellow River estuary. Biological processes had opposite effects on Ωarag, whereby elevated biological production led to the highest Ωarag in the South Yellow Sea surface water, whereas net community respiration/remineralization induced low Ωarag in subsurface water. Stratification affected the level and scale of low Ωarag in subsurface water. By the year 2100, surface water with Ωarag > 2.0 will disappear except for the Yellow River estuary, and most of the subsurface water will develop substantial aragonite undersaturation. Highlights: Dynamics of seawater Ωarag were investigated in the BoHai and Yellow seas. Riverine freshwater input decreased Ωarag in the Changjiang and Yalu river estuaries. Freshwater input from the Yellow River induced high Ωarag in the estuary. Seawater with Ωarag above 2.0 will likely disappear by the year 2100.